Geopolitics, Aid and Growth - Axel Dreher; Vera Eichenauer; Kai Gehring (University of Heidelberg, Department of Economics, 2014)
We investigate the effects of short-term political motivations on the effectiveness of foreign aid. Specifically, we test whether the effect of aid on economic growth is reduced by the share of years a country has served on the United Nations Security Council (UNSC) in the period the aid has been committed, which provides quasi-random variation in aid. Our results show that the relationship of aid with growth is significantly lower when aid has been committed during a country's tenure on the UNSC. We derive two conclusions from this. First, short-term political favoritism reduces growth. Second, political interest variables are inadequate as instruments for overall aid, raising doubts about a large number of results in the aid effectiveness literature.
urn:nbn:de:bsz:16-heidok-175459
Keywords: 330; aid effectiveness; economic growth; politics and aid; United Nations Security Council membership; political instruments